2015
DOI: 10.1155/2015/513761
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium Ion Exchanged Zeolite for Laser Desorption/Ionization Mass Spectrometry of Phosphorylated Peptides

Abstract: α-Cyano-4-hydroxycinnamic acid (CHCA), an organic matrix molecule for matrix-assisted laser desorption/ionization mass spectrometry, was adsorbed to NH4 +-type zeolite surface, and this new matrix was used for the detection of low-molecular-weight compounds. It was found that this matrix could simplify the mass spectrum in the low-molecular-weight region and prevent interference from fragments and alkali metal ion adducted species. CHCA adsorbed to NH4 +-type ZSM5 zeolite (CHCA/NH4ZSM5) was used to measure atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…For example, unesterified cholesterol, commonly detected at 386 m/z or 369 m/z (M + H -H2O) using this method (Schiller, Zschornig et al 2001) was detected in MALDI-TOF MS but was not confirmed using MALDI-TOF MS/MS. It is possible that the matrix used (2,5-DHB) for analysis had too many matrix-related low mass peaks corresponding to it, making identification of unesterified cholesterol problematic (Yang and Fujino 2015). An additional limitation is the quantification of lipids using MALDI-TOF MS. Quantification can be difficult as crystallisation of the analyte and matrix does not form a uniform layer over the target surface, therefore signals from the analyte may be variable (Duncan, Roder et al 2008).…”
Section: Lipid Analysismentioning
confidence: 99%
“…For example, unesterified cholesterol, commonly detected at 386 m/z or 369 m/z (M + H -H2O) using this method (Schiller, Zschornig et al 2001) was detected in MALDI-TOF MS but was not confirmed using MALDI-TOF MS/MS. It is possible that the matrix used (2,5-DHB) for analysis had too many matrix-related low mass peaks corresponding to it, making identification of unesterified cholesterol problematic (Yang and Fujino 2015). An additional limitation is the quantification of lipids using MALDI-TOF MS. Quantification can be difficult as crystallisation of the analyte and matrix does not form a uniform layer over the target surface, therefore signals from the analyte may be variable (Duncan, Roder et al 2008).…”
Section: Lipid Analysismentioning
confidence: 99%